2008
DOI: 10.4028/www.scientific.net/amr.43.97
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Analysis of Machining Processes for Light-Weight Aluminium Structures

Abstract: Abstract. Different possible reasons for defects have to be considered in machining light-weight aluminum structures. In the machining process, the cutting power affecting the workpiece leads to a thermo-mechanical load that can cause undesirable workpiece deformations and thus shape deviations. Moreover, the microstructure and the machined surface can be influenced, which is detrimental to the later application of the structures. Previously conducted experimental and simulative investigations, estimated the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…There has been a lot of research on deformation problems with thin-walled components by domestic and foreign scholars. Weinert [4,5] used finite element method for numerical analysis of the processing process of components and proposed an optimized processing strategy to control processing deformation. Liao Kai [6] measured the initial residual stress of aluminum alloy thin-walled frame members using the layered-cutting method and established a mechanical model of the influence of initial residual stress and processing residual stress on deformation.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a lot of research on deformation problems with thin-walled components by domestic and foreign scholars. Weinert [4,5] used finite element method for numerical analysis of the processing process of components and proposed an optimized processing strategy to control processing deformation. Liao Kai [6] measured the initial residual stress of aluminum alloy thin-walled frame members using the layered-cutting method and established a mechanical model of the influence of initial residual stress and processing residual stress on deformation.…”
Section: Introductionmentioning
confidence: 99%
“…So far, this modelling technique is lagging the ability to simulate the chip or burr formation. Here, the main aspect is on the analysis of the work-piece deformation and geometrical deviations [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, a limited number of studies on the MMCs reinforced with Al 2 O 3 particles have been reported with respect to tool wear, surface finish, particle size and volume fraction of particles using coated cutting tools. 8,[33][34][35][36] The main concern, when machining MMCs, is the extremely high tool wear due to the abrasive action of the ceramic particles. Therefore, materials of very high resistance to abrasive wear are often recommended.…”
Section: Introductionmentioning
confidence: 99%